KRITIK SOSIAL TERHADAP SISTEM HUKUM DALAM NOVEL BUKAN KARENA KAU KARYA TOHA MOHTAR (Sebuah Tinjauan Sosiologis) - Waluyo, Sukarjo (HUMANIKA, 2014)
The research entitled â€œ Critical Social of Law System in The Novel Bukan Kerena Kau, by Toha Mohtar (A Sociological Analysis)â€ intends to tell the critical social in law system which has been occurredÂ  at that time as the novel written. Critical social is one of literature critics which specially studies literature using social aspects in its consideration. Sociologically, BKK novelÂ  is a very interesting novel because it is able to tell the critical social in its story. In the novel, we can see the poor of social livingÂ  situation and condition . It is in line with Indonesia history which the people have just been independent. The critical social ofÂ  law systemÂ  has not revealed the involvement of law as a social control device and a means to expedite the process of social interaction.